The The Impact of Problem-Based Workshops on Improving Teacher Competency in Designing Learning Based on Environmental Potential - Fatni Mufit (Fakultas MIPA Universitas Negeri Padang, 2020)
The competence of science teachers in Padang City Junior High Schools in developing learning tools is still low, as revealed by the teacher's pre-test abilities before the workshop is held. Pre-test includes gathering information about learning resources, learning media, models / methods / approaches, and assessment instruments used by teachers not yet utilizing the environment. Referring to the problems of teachers, problem-based workshop activities are designed in an effort to improve teacher competencies in designing learning tools based on environmental potential. Problem-based workshops have stages: (1) problem identification, (2) Focusing on problems, (3) Finding alternative solutions, (4) Presentation of solutions; (5) Implementation and (6) Reflection & follow-up. The workshop was attended by 20 junior high school science teachers in Padang city. The workshop activities consisted of 2 parts, namely the workshop activities at FMIPA UNP and the Implementation activities at SMP 25 Padang. Problem-based workshops succeeded in increasing teacher competence in designing IPA-based environmental learning tools. The results of the implementation of the workshop products by the teacher showed a positive influence on student involvement and activity in learning